EVALUASI PELAKSANAAN SISTEM ADMINISTRASI AKADEMIK IAIN SAMARINDA - Riswan, Riswan (Idaarah: Jurnal Manajemen Pendidikan, 2020)
This study aims to evaluate the academic administration system at IAIN Samarinda. This research is a qualitative research with a descriptive approach. The data collection techniques used were interviews, document study and observation. The data obtained were then analyzed qualitatively by referring to standard theories and concepts. The results of the data analysis are then compiled so that a general conclusion of the study can be obtained. The results of the research on the implementation of the academic administration system at IAIN Samarinda show: (1) Planning has not been carried out thoroughly, it can be seen from the incomplete guidelines for the academic administration system, so that at the implementation stage there are many inconsistencies; (2) Inter-unit coordination has not been implemented in an integrated manner so that many students experience confusion and uncertainty in information; (3) There is still overlap in the implementation of the academic administration system by task stakeholders, even though it is not the main task and function; (4) Monitoring and evaluation has not been carried out programmatically. The main obstacles in implementing the academic administration system at IAIN Samarinda are managerial, the academic administration system that is not yet integrated, and commitment to provide the best service to students.